NUMERICAL RESPONSE AND EFFICIENCY OF CONVERSION OF INGESTED FOOD OF PREDATOR Dicrodiplosis manihoti Harris, (DIPTERA : CECIDOMYIIDAE) FOR EGGS DENSITIES OF MEALY BUG Planococcus citri (Risso),(HEMIPTERA :PSEUDOCOCCIDAE) . - & Al-Shammari, Al-Zubaidy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The results of numerical response showed to increasing rates of egg production for the predator female with prey density increases, noting of a positive correlation between the number of eggs lying by the female predator and prey density, Being 7, 13.1, 17 and 30 eggs/female during her life when making egg densities of prey 10, 20, 40 and 60 eggs/day during the period of development of Larval ages respectively.  Statistical analysis results have pointed to the moral differences between those rates at 0.05 probability level. Food conversion efficiency was marked by ECI also increases with increasing density of prey . Food conversion efficiency to  eggs by female predator increased  in high densities of prey compared with low  densities as well as reduced food efficiency with increasing density of prey  where when lying densities and decreased when high densities prey. It also shortened the duration of phases three predator when prey density increases amounting to (2.74, 3.37, 9.15) and(1.62, 4.32, 5.04), (1.86, 2.82, 4.07) and (1.16 , 2.89, 3.42) consecutive days so that the total duration of Larval stage 15.26, 10.98, 8.75 and 7.47 days respectively with high significance deference. As well as high rates of predation 80, 74.24, 96.52 and 116.91 egg respectively and moral difference in egg consumption rates between larval stages as well as during the period of Larval stages  at probability 0.05.  survival rates also increased  for the  larval, pupal  and   adults stages  when the density of the prey increased  with high  significance  difference.